2007
DOI: 10.1007/s00424-007-0300-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of DIDS, NPPB, and phloretin on intracellular chloride channels

Abstract: We studied the effects of the chloride channel blockers, 5-nitro-2-(phenylpropylamino)-benzoate (NPPB), dihydro-4,4' diisothiocyanostilbene-2,2'-disulphonic acid (DIDS), and phloretin on H2O2-induced primary culture cardiomyocyte apoptosis and activity of intracellular chloride channels obtained from rat heart mitochondrial and lysosomal vesicles. The chloride channel blockers (100 micromol/l) inhibited the H2O2-induced cardiomyocytes apoptosis. We characterized the effect of the blockers on single channel pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…The present study on cardiomyocytes showed that STS resulted in a significant decrease in cell viability accompanied by typical apoptotic characteristics and these apoptotic events were prominently suppressed by DIDS, which is consistent with previous reports [18,19]. Several studies demonstrated various Cl -transport pathways including the VSOR Cl -channel which is closely related to cell volume changes, are involved in the development of apoptosis [5,22] and DIDS was found to exert its cytoprotection by preventing the early-phase apoptotic cell shrinkage via inhibition of Cl [5,23]. However, several recent studies demonstrated that the rescue of DIDS on cardiomyocyte apoptosis is mainly mediated by inhibition of chloride channels, because a bicarbonate-free condition which minimizes the function of Cl -/HCO 3 -exchangers failed to affect the cytoprotective effect of DIDS on STSinduced apoptosis in rat cardiomyocytes [18], as well as STS-induced [19] and ischemia-reperfusion-induced apoptosis in mouse cardiomyocytes [9].…”
Section: Discussionsupporting
confidence: 87%
“…The present study on cardiomyocytes showed that STS resulted in a significant decrease in cell viability accompanied by typical apoptotic characteristics and these apoptotic events were prominently suppressed by DIDS, which is consistent with previous reports [18,19]. Several studies demonstrated various Cl -transport pathways including the VSOR Cl -channel which is closely related to cell volume changes, are involved in the development of apoptosis [5,22] and DIDS was found to exert its cytoprotection by preventing the early-phase apoptotic cell shrinkage via inhibition of Cl [5,23]. However, several recent studies demonstrated that the rescue of DIDS on cardiomyocyte apoptosis is mainly mediated by inhibition of chloride channels, because a bicarbonate-free condition which minimizes the function of Cl -/HCO 3 -exchangers failed to affect the cytoprotective effect of DIDS on STSinduced apoptosis in rat cardiomyocytes [18], as well as STS-induced [19] and ischemia-reperfusion-induced apoptosis in mouse cardiomyocytes [9].…”
Section: Discussionsupporting
confidence: 87%
“…It was reported that procyanidins induces necrosis and apoptosis of prostate cancer cell 'PC-3' for 6 and 24 hr with different concentration (100-300 µg ml -1 ) of procyanidins (Shang et al 2009). Studies also revealed the apoptotic and cardioprotective properties of phloretin on H 2 O 2 -induced primary culture (Malekova et al 2007). Phloretin demonstrated strong anti-tumor effects by inhibiting the growth of several cancer cell lines (Kobori et al 1999).…”
Section: Biological Properties Of Apple Phenolicsmentioning
confidence: 97%
“…Phloretin (2',4',6'-trihydroxy-3-(4-hydroxyphenyl)-propiophenone), a component of apples, pears and strawberries [1,2], is a dipolar small molecule interfering with diverse channels and transporters [3,4,5,6,7,8,9,10] including glucose transporters [1,2]. Effects of Phloretin include decrease of oxidative stress [11], inhibition of inflammation [12], increase endothelial nitric oxide production and vasodilation [13,14], downregulation of endothelial adhesion molecules [15], and inhibition of platelet activation [15].…”
Section: Introductionmentioning
confidence: 99%